2012
DOI: 10.1074/jbc.m112.353128
|View full text |Cite
|
Sign up to set email alerts
|

Galactosylated Fucose Epitopes in Nematodes

Abstract: Background: Galactosylation of core fucose residues is a peculiar feature of invertebrate N-glycans. Results: Two variants of galactosylated fucose were observed in a Caenorhabditis elegans mutant and in two nematode parasites. Conclusion: Galactosylation of fucose in nematodes is more widespread than previously thought and is affected by processing hexosaminidases. Significance: Galactosylated fucose motifs may present new targets for anthelminthic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(66 citation statements)
references
References 45 publications
4
62
0
Order By: Relevance
“…The penultimate GlcNAc residue of D1, D3, and D4 are modified with a Hex-Fuc disaccharide, which is presumed to be Gala1-2Fuc. 8 This disaccharide moiety, however, does not affect the interaction, because D4egalactose, which contains this disaccharide unit, was not bound by the antibody. This disaccharide unit was also shown to have no effect on the interaction with the antibody, because no difference was observed between the elution profiles of D4 and E4, though D4 contains this disaccharide unit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The penultimate GlcNAc residue of D1, D3, and D4 are modified with a Hex-Fuc disaccharide, which is presumed to be Gala1-2Fuc. 8 This disaccharide moiety, however, does not affect the interaction, because D4egalactose, which contains this disaccharide unit, was not bound by the antibody. This disaccharide unit was also shown to have no effect on the interaction with the antibody, because no difference was observed between the elution profiles of D4 and E4, though D4 contains this disaccharide unit.…”
Section: Resultsmentioning
confidence: 99%
“…Galb1-4Fuc is a unique disaccharide unit found only in N-glycans of protostomia, 2,8 and some of its roles have been demonstrated in the free-living nematode Caenorhabditis elegans, which is widely used as a multicellular model organism and also as a model of parasitic nematodes. 9 We and others previously demonstrated that Galb1-4Fuc is an endogenous recognition unit of the C. elegans galectin LEC-6.…”
Section: Introductionmentioning
confidence: 99%
“…Besides these proteins from C. cinerea, galectins from two different Agrocybe species: ACG from Agrocybe cylindracea and AAG from Agrocybe aegerita, have been characterized (Yagi et al 2001;Yang et al 2009) (Table 1). The latter two share 88 % sequence identity Butschi et al 2010;Cooper et al 1997;Titz et al 2009;Walser et al 2004;Yan et al 2012) Gal-β1,4-GlcNAc Gal-β1,4-Glc na nd (Luan et al 2010;Yang et al 2009;Yang et al 2005a;Yang et al 2005b;Yang et al 2005c) ACG Agrocybe cylindracea 160 aa…”
Section: Galectinsmentioning
confidence: 99%
“…XCL is toxic toward the hemipterans A. pisum and Myzus persicae, the dipterans Drosophila melanogaster and A. aegypti, as well as the nematode C. elegans (BleulerMartinez et al 2011;Jaber et al 2008;Trigueros et al 2003). Both the entomotoxic and nematotoxic activity of XCL are dependent on carbohydrate binding, and genetic data suggested that XCL binds to terminal GlcNAc residues in nematode N-glycans (Jaber et al 2008;Yan et al 2012). TAP1 is toxic to C. elegans, A. aegypti, and the amoebozoon A. castellanii .…”
Section: Actinoporin-type Lectinsmentioning
confidence: 99%
See 1 more Smart Citation